Benefiting from Open Innovation: A Multidimensional Model of Absorptive Capacity*. Issue 3 (19th December 2016) - Zobel, Ann‐Kristin
Abstract : While recent studies shed some light on the performance implications of open innovation, there is a gap in understanding how firms can translate their openness into innovation outcomes. In particular, it is unclear whether—and if so, how—firms can create a competitive advantage in product innovation by tapping into external sources of innovation. To address this gap, this study conceptualizes multidimensional components of absorptive capacity and develops a nomological network that explicates relationships between these components and competitive advantage in product innovation. By marrying the open innovation and absorptive capacity perspectives, higher‐order models of absorptive capacity are proposed which delineate the underlying processes to recognize, assimilate, and exploit external sources of innovation. The empirical analysis of the nomological network based on original survey data reveals important findings. First, there is a positive indirect baseline association between external technological resource access and competitive advantage in product innovation, mediated by the firm's technology‐related capabilities. Second, components of absorptive capacity modify this indirect baseline relationship. Recognition capacity is positively associated with external technological resource access and therefore, operates as an antecedent to the proposed baseline relationship. Assimilation capacity constitutes a relevant condition to the proposed baseline relationship. The indirect association between external technological resource access and competitive advantage in product innovation is dependent on the level of assimilation capacity. Exploitation capacity has an additional and independent direct positive association with competitive advantage in product innovation. This study contributes to the open innovation literature by delineating organizational processes that help to explain interfirm differences in benefiting from external sources of innovation. In addition, this study adds to the absorptive capacity literature by developing and validating a set of measures that captures, individually and in concert, three components of absorptive capacity.